Report of a case of Raine syndrome and literature review. (14th May 2015) - Seidahmed, Mohammed Zain; Alazami, Anas M.; Abdelbasit, Omer Bashir; Al Hussein, Khalid; Miqdad, Abeer M.; Abu‐Sa'da, Omar; Mustafa, Tareq; Bahjat, Sarah; Alkuraya, Fowzan S.
Abstract : We report on a case of Raine syndrome with a mutation in FAM20C and typical phenotypic features consisting of midface hypoplasia, hypoplastic nose, choanal atresia, wide fontanelle, exophthalmos, generalized osteosclerosis and intracranial calcification. New features in our patient are cerebellar hypoplasia and pachygyria. We review the literature and conclude that the triad of hypoplastic nose, exophthalmos and generalized osteosclerosis and/or intracranial calcification is consistent in all molecularly confirmed cases. © 2015 Wiley Periodicals, Inc.